2008
DOI: 10.1103/physrevlett.100.096102
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vibrational Resonances of Water-Vapor Interfaces by Phase-Sensitive Sum-Frequency Spectroscopy

Abstract: Phase-sensitive sum-frequency spectroscopy provides correct characterization of vibrational resonances of water-vapor interfaces and allows better identification of interfacial water species contributing to different parts of the spectra. Iodine ions emerging at an interface create a surface field that tends to reorient the more loosely bonded water molecules below the topmost layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
450
4
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 326 publications
(499 citation statements)
references
References 25 publications
44
450
4
1
Order By: Relevance
“…To facilitate the discussion, therefore, we need to briefly review the spectra and structure of the neat water/vapor interface deduced from our earlier PS-SFVS measurement. 22 We have found that while the We now compare the spectra of water/vapor interfaces of aqueous solutions with those of neat water. The spectral change then allows us to learn how ions emerging at the interfaces perturb the interfacial structure.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…To facilitate the discussion, therefore, we need to briefly review the spectra and structure of the neat water/vapor interface deduced from our earlier PS-SFVS measurement. 22 We have found that while the We now compare the spectra of water/vapor interfaces of aqueous solutions with those of neat water. The spectral change then allows us to learn how ions emerging at the interfaces perturb the interfacial structure.…”
Section: Discussionmentioning
confidence: 90%
“…From previous SFVS studies of NaI solution, 22 it is known that I -ions prefer to come to the surface and create a negative surface field. The spectral change with respect to the neat water interface mainly comes from the surface field reorienting the interfacial DDAA water molecules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative interpretation, which is subject to ongoing scientific discussion Shen, 2008, 2009], assigns the whole band to a Fermi resonance resulting from an intramolecular coupling of a stretch vibration with a bending mode overtone vibration of water [Sovago et al, 2008]. Very recently, stimulated by new experimental results of a phase-sensitive VSFG study [Ji et al, 2008], Fan et al [2009] presented yet another interpretation based on molecular dynamics calculations. According to their consistent two-layer model of interfacial water, the broad spectral feature is made up of four distinct types of hydrogen bond stretches peaking at 3117 cm −1 ("upward" pointing OH in layer II, ice like), 3222 cm −1 ("downward" pointing OH in layer I, ice like), 3448 cm −1 (downward pointing OH in layer II, liquid like), and 3696 cm −1 (upward pointing OH in layer I, dangling OH).…”
Section: Oh Spectral Range 321 General Spectral Trendsmentioning
confidence: 99%